Opioid transdermal delivery system: a useful method for pain management in children - Mastrangelo, Stefano (Ann Transl Med, 2021)
Transdermal delivery system (TDDS) is a non-invasive and less expensive method for drug delivery. Despite its feasibility, only a restricted group of drugs can be delivered by TDDS, because of the little permeability of skin. Moreover, TDDS is limited to lipophilic drugs with small molecular masses and it is not indicated for peptides, macromolecules and hydrophilic drugs. Among opioids, fentanyl and buprenorphine are suitable for transdermal administration only for chronic pain management (not for acute pain). However, opioid TDDS still remains off-label for chronic pain management in children. In this review, we describe the main features of the adhesive TDDS and the main characteristics of pediatric skin and the differences from the adult one. Moreover, we focus on fentanyl and buprenorphine patches and their non-invasive mechanism of action, and on the main aspects that make them suitable for pain management among the pediatric population.